Safe patient handling behaviors and lift use among hospital nurses: A cross-sectional study. (September 2017) - Lee, Soo-Jeong; Lee, Joung Hee
Abstract: Purpose: Patient handling is well known for the risk of musculoskeletal injury. Safe work practices are important to reduce risk of injury while performing patient handling tasks. This study investigated factors associated with safe patient handling behaviors and lift use among hospital nurses in the United States. Methods: This study analyzed cross-sectional survey data from a statewide random sample of 221 hospital nurses in California who had patient handling duties. Safe patient handling behaviors and lift use were examined for the relationships with demographic characteristics, organizational safety practices, physical and psychosocial job factors, musculoskeletal symptoms, and perceptions about lift use and risk of injury. Results: In multivariable logistic regression, high safe patient handling behaviors were significantly associated with a positive organizational safety climate (Odds Ratio [OR] = 2.76, 95% Confidence Interval [CI] 1.51–5.03), people-oriented culture (OR = 2.59, 95% CI 1.45–4.62), and ergonomic practices (OR = 1.67, 95% CI 1.04–2.67). High lift use (>50% of the time when needed) were significantly associated with high lift availability (OR = 3.1, 95% CI 1.06–9.01) and positive perceptions about lift use (OR = 3.48, 95% CI 1.63–7.44). In bivariate analysis, high safe patient handling behaviors were associated with shorter height, non-White race, lower physical workload, lower job strain, higher job satisfaction, and less musculoskeletal symptoms. Conclusions: The study findings underscore the importance of organizational safety practices and culture to promote safe work practices for patient handling injury prevention. Also, making lift equipment readily available and improving positive perceptions and experiences about lifts can be crucial to ensure the use of lift equipment.